Risky driving behaviour in urban Ghana: the contributions of fatalistic beliefs, risk perception, and risk-taking attitude - Teye-Kwadjo, E. (International Journal of Health Promotion and Education, 2019)
There is rapid motorisation in Ghana, leading to increases in risky driving and road crashes. Understanding pathways through which traffic risk perception and traffic fatalism affects risky driving behaviour can help with effective road safety education and health promotion interventions among drivers in Ghana. Yet, the pathways are not well understood. Structural equation modelling (SEM) was conducted to assess the hypothesised model that attitudes towards risky driving would mediate the association of traffic fatalism and traffic risk perception with risky driving behaviour. Licensed drivers (N = 519) aged 18 to 73 years (M = 27.98, SD = 9.23) completed a survey on fatalistic beliefs, traffic risk perception, and risky driving attitudes and self-reported risky driving behaviour. The model shows a good fit to the data. Attitudes towards risky driving mediated the effects of fatalistic beliefs and risk perception on risky driving behaviour. Further, fatalistic beliefs were positively associated with attitudes towards risky driving. Risk perception was negatively associated with attitudes towards risky driving. Moreover, attitudes towards risky driving positively predicted risky driving behaviour. Other multivariate results showed that risk perception and risk-taking differ among male and female drivers and among married and never married drivers. The results provide opportunities for the National Road Safety Commission to design safety promotion interventions to target the belief that road crashes are influenced, in part, by fate and destiny other than by road user behaviour. Road safety education should target favourable attitudes towards risk-taking through which fatalistic beliefs and risk perception affect driving behaviour. © 2019, © 2019 Institute of Health Promotion and Education.
Keywords: fatalism; health promotion; Risk perception; risky driving; road safety; structural equation modelling